Experimental near-infrared spectroscopy-guided minimally invasive segmental artery occlusion. (4th February 2021) - von Aspern, Konstantin; Haunschild, Josephina; Heier, Marcus; Ossmann, Susann; Mohr, Friedrich W; Borger, Michael A; Etz, Christian D
Abstract: OBJECTIVES: Minimally invasive staged segmental artery (SA) coil- and plug embolization is a new method for paraplegia prevention associated with extensive aortic procedures. Near-infrared spectroscopy of the paraspinal collateral network (cnNIRS) has emerged as a non-invasive method for spinal cord monitoring. The aim of this study was to evaluate cnNIRS to guide minimally invasive SA occlusion. METHODS: In a chronic large animal experiment, 18 juvenile pigs underwent two-stage minimally invasive staged SA coil- and plug embolization for complete SA occlusion. Coil-embolization was performed either by SA main stem occlusion (characteristic of pig anatomy) or separately for the left- and right SA. Lumbar cnNIRS was recorded during and after the procedure. Neurological status was assessed up to 3 days after complete SA occlusion. RESULTS: Mean time from SA coil embolization to minimum cnNIRS values was 11 ± 5 min with an average decrease from 101 ± 2% to 78 ± 8% of baseline (difference: −23 ± 9, P  < 0.001). Lumbar cnNIRS demonstrated significant differences between left and right when SAs were occluded separately in all cases (−7 ± 4%, 1 min after first SA occlusion; P  = 0.001). Permanent paraplegia occurred in 2 (11%) and any kind of neurological deficit—temporary or permanent—in 7 animals (39%). Association between lumbar cnNIRS and neurological outcome after minimally invasive staged SA coil- and plug embolization suggests positive correlation ( R  = 0.5, P  = 0.052). CONCLUSIONS: Lumbar cnNIRS independently reacts to unilateral SA occlusion. cnNIRS-guided SA occlusion is feasible and may become a useful adjunct facilitating adequate and complete vessel occlusion.